A Phenomenological Exploration of Diversity in Counselor Education. Issue 1 (2nd January 2018) - Foxx, Sejal Parikh; Kennedy, Stephen D.; Dameron, Merry Leigh; Bryant, Amber
ABSTRACT: The purpose of this phenomenological study was to describe how racial and ethnic minority students chose to research, apply to, and accept invitations into one counselor education doctoral program. Interviews with 9 participants revealed the following 4 themes: (a) emphasis of diversity, (b) location, (c) need for employment and/or financial assistance, and (d) relationships with faculty. This study also explores implications related to the recruitment and retention of racial and ethnic minorities in counselor education programs.